Expression of PAFR as Part of a Prosurvival Response to Chemotherapy: A Novel Target for Combination Therapy in Melanoma - Ana Claudia Onuchic; Camila M. L. Machado; Renata F. Saito; Francisco J. Rios; Sônia Jancar; Roger Chammas (Mediators of Inflammation)
Melanoma cells express the platelet-activating factor receptor (PAFR) and, thus, respond to PAF, a bioactive lipid produced by both tumour cells and those in the tumour microenvironment such as macrophages. Here, we show that treatment of a human melanoma SKmel37 cell line with cisplatin led to increased expression of PAFR and its accumulation. In the presence of exogenous PAF, melanoma cells were significantly more resistant to cisplatin-induced cell death. Inhibition of PAFR-dependent signalling pathways by a PAFR antagonist (WEB2086) showed chemosensitisation of melanoma cells in vitro. Nude mice were inoculated with SKmel37 cells and treated with cisplatin and WEB2086. Animals treated with both agents showed significantly decreased tumour growth compared to the control group and groups treated with only one agent. PAFR accumulation and signalling are part of a prosurvival program of melanoma cells, therefore constituting a promising target for combination therapy for melanomas.